A detailed analysis of the effect of repetitive transcranial magnetic stimulation on negative symptoms of schizophrenia: a double-blind trial - Prikryl, Radovan; Ustohal, Libor; Prikrylova Kucerova, Hana; Kasparek, Tomas; Venclikova, Simona; Vrzalova, Michaela; Ceskova, Eva (Schizophrenia research, 2013)
OBJECTIVE: The aim of the study was to assess the effect of rTMS not only on the general severity of negative schizophrenia symptoms, but also particularly on their individual domains, such as affective flattening or blunting, alogia, avolition or apathy, anhedonia, and impaired attention. METHODS: Forty schizophrenic male patients on stable antipsychotic medication with prominent negative symptoms were included in the study. They were divided into two groups: 23 were treated with active and 17 with placebo rTMS. Both treatments were similar, but placebo rTMS was administered using a purpose-built sham coil. Stimulation was applied to the left dorsolateral prefrontal cortex (DLPFC). The stimulation frequency was 10 Hz; stimulation intensity was 110% of the individual motor threshold intensity. Each patient received 15 rTMS sessions on 15 consecutive working days (five working days "on" and two weekend days "off" design). Each daily session consisted of 20 applications of 10-second duration with 30-second intervals between sequences. The patients and raters were blind to condition of stimulation treatment. RESULTS: The active rTMS led to a statistically significantly higher reduction of the Scale for the Assessment of Negative Symptoms (SANS) total score and of all domains of negative symptoms of schizophrenia. After Bonferroni adjustments for multiple testing, the statistical significance disappeared in alogia only. CONCLUSION: High-frequency rTMS stimulation over the left DLPFC at a high stimulation intensity with a sufficient number of applied stimulating pulses may represent an efficient augmentation of antipsychotics in alleviating the negative symptoms of schizophrenia.
Keywords: Repetitive transcranial magnetic stimulation; Humans; rTMS; Double-Blind Method; schizofrenie; Female; analýza rozptylu; dospělí; mladý dospělý; Analysis of Variance; Psychiatric Status Rating Scales; výsledek terapie; Prefrontal cortex; dvojitá slepá metoda; lidé; transkraniální magnetická stimulace; Schizophrenia; Electromyography; Adult; ženské pohlaví; psychiatrické posuzovací škály; Male; High-frequency; Treatment Outcome; Transcranial Magnetic Stimulation; Young Adult; Negative symptoms; mužské pohlaví; elektromyografie; SANS